Didactic component of teaching foreign languages on future profession: formation of communicational and translation skills - Garnyk, Liudmyla Petrivna; Snihurova, Irina Ivanivna (My University, 2021)
Nowadays higher education focuses on development of learner’s personality, whose proficiency and intellectual potential grounds on obtained knowledge, high moral values, communicative skills, foreign languages mastery, social mobility and competitiveness on labor market. Critical observe and evaluation of adequacy existed didactic component in this area were inspired by statement that your knowledge and cognitive skills can set you apart, due to what you know today will be out-of-date sooner than you even can imagine. Obtained results can be useful for educators and language teachers who work on design and modernization of foreign language teaching process in university.
Keywords: communicational and translator’s skills; educational management; teaching foreign languages on future profession; didactic component; cross-cultural communication